Ultra-Sensitive HIV-1 Latency Viral Outgrowth Assays Using Humanized Mice - Schmitt, Kimberly; Akkina, Ramesh (Frontiers in Immunology, 2018)
In the current quest for a complete cure for HIV/AIDS, highly sensitive HIV latency detection methods are critical to verify full viral eradication. Until now, the in vitro quantitative viral out growth assays (qVOA) have been the gold standard for assessing latent HIV-1 viral burden. However, these assays have been inadequate in detecting the presence of ultra-low levels of latent virus in a number of patients who were initially thought to have been cured but eventually showed viral rebound. In this context, new approaches utilizing in vivo mouse-based VOAs are promising. In the murine VOA (mVOA), large numbers of CD4+ T cells or PBMC from aviremic subjects are xenografted into immunodeficient NSG mice whereas in the humanized mouse VOA (hmVOA) assay, patient CD4+ T cell samples are injected into BLT or hu-HSC humanized mice. While latent virus could be recovered in both of these systems, the hmVOA provides higher sensitivity than the mVOA using fewer number of input cells. In contrast to the mVOA, the hmVOA provides a broader spectrum of highly susceptible HIV-1 target cells and enables newly engrafted cells to home into preformed human lymphoid organs where they can infect cells in situ after viral activation. Hu-mice also allow for both xenograft and allograft driven cell expansion with less severe GvH providing a longer time frame for potential viral outgrowth from cells with a delayed latent viral activation. Based on these advantages, the hmVOA has great potential in playing an important role in HIV latency and cure research.